Program “Generasi Z Melek Financial” dalam Meningkatkan Literasi Keuangan Siswa SMP Islam Terpadu Ngasem - Hidayat, Taufiq; Rohman, Nur; Astuti, Rika Pristian Fitri; Zuhriah, Fifi; Damayanto, Ahmad Dikky (IKIP PGRI Bojonegoro, 2025)
ABSTRACT This program aims to improve financial literacy among teenagers through a participatory and contextual approach that is relevant to the digital world. This activity was carried out in the form of interactive workshops using discussion, simulation, and reflection methods, involving 36 ninth-grade students. The results of the pre-test and post-test showed a 51.3% increase in financial literacy understanding, accompanied by behavioral changes such as an increase in saving motivation, the ability to distinguish between needs and wants, and control over impulsive purchases due to the influence of social media. This program also fostered critical awareness of the Fear of Missing Out (FOMO) phenomenon and gave birth to the School Financial Friends community as a form of activity sustainability. Overall, this activity was effective in shaping wise economic behavior by strengthening the financial capacity of the younger generation in the digital era. Keywords: Financial literacy, Generation Z, fear of missing out, digital era, social media ABSTRAK Program ini bertujuan meningkatkan literasi keuangan remaja melalui pendekatan partisipatif dan kontekstual yang relevan dengan dunia digital. Kegiatan ini dilaksanakan dalam bentuk workshop interaktif dengan metode diskusi, simulasi, dan refleksi, melibatkan 36 siswa kelas IX. Hasil pre-test dan post-test menunjukkan peningkatan pemahaman literasi keuangan sebesar 51,3%, disertai perubahan perilaku seperti meningkatnya motivasi menabung, kemampuan membedakan kebutuhan dan keinginan, serta pengendalian pembelian impulsif akibat pengaruh media sosial. Program ini juga menumbuhkan kesadaran kritis terhadap fenomena Fear of Missing Out (FOMO) dan melahirkan komunitas Sahabat Finansial Sekolah sebagai bentuk keberlanjutan kegiatan. Secara keseluruhan, kegiatan ini efektif membentuk perilaku ekonomi yang bijak melalui penguatan kapasitas finansial generasi muda di era digital. Kata kunci: Literasi keuangan, Generasi Z, fear of missing out, era digital, media sosial